Review of traffic control algorithms in computer networks - Barczak, Andrzej; Sitkiewicz, Tomasz (Studia Informatica. System and information technology, 2008)
This paper presents comparison of popular traffic control algorithms in computer networks. It also contains descriptions of functioning of these algorithms. The first part of this paper contains description of evaluation criteria of traffic control algorithms (from system and user viewpoint). The second part of article contains description of new algorithms, which are theoretically improved or brand new, just introduced for practical use. These algorithms are developmental and eliminate disadvantages of already existing algorithms. The third part of this paper contains description of classical algorithms, which are well known, described and researched. It contains also propositions of modifications of classical linear programming algorithms. These modifications are for adjusting these algorithms to described problem.